Os operadores de contraposição no gênero resumo acadêmico: perspectiva linguístico-discursiva - Silva, Marcos Antônio da (2016)
The present study is guided by the Language Argument Theory (LAT), postulated by Jean-Claude Anscombre/Oswald Ducrot (1994) and Ducrot (1987, 1988). More specifically, in the standard version, the third stage, “The language as a constituent of meaning” and also in the Topoi Theory. The central thesis of this theory concerns that in the own language structure there are elements that present argumentative values, and, because of this, they have the responsibility for enabling or not the continuity of the discourse. Therefore, these elements, named by the authors of argumentative semantics as argumentative operators, have the function for orienting the statements to particular and possible conclusions. Also postulated by Ducrot, subsidizes our research the Polyphonic Theory of Enunciation, that aims to question the principle of the speaking subject uniqueness. For the Ducrotian Polyphonic Theory, it is through the presence of some linguistic elements, in the discourses, that the enunciators are put on the scene. In addition to the LAT studies, we present, briefly, some principles about the studies of discursive modalization, considering the relevance of the modalizers elements on the speaker behavior in the face of enunciators, in some cases, during our analysis. Thus, authors like Castilho and Castilho (1993), Cervoni (1989), Neves (2010), Nascimento (2005, 2012), among others, will be present in our theoretical framework about these studies. Based on the Argument Theory in language and the phenomenon of the discursive modalization, our objective, in this research, is to realize an analysis and a description of the semantic-argumentative functioning of contrapositive operators in the academic abstract genre, from a linguistic-discursive perspective. The methodology used in this study is descriptive and quanti-qualitative, since we will be attentive not only to the functioning of these operators, but also to the quantity of times that the referred elements occur. The corpus, here in analysis, is constituted by 300 academic abstracts published in annals and magazines with scientific-academic character. The results indicate a predominance of the use of contrapositive operators with the masPA function, to the detriment of operators with function masSN. Furthermore, it is pertinent to punctuate that this research expands what is proposed by Ducrot (1988), about the possibilities of the speaker positioning in the face of enunciators – this author points only to the rebound, approval and identification – once we found the existence of two species of rebound: total and partial. Still in relation to the analysis, we identify the important presence of topos and information shared in the abstracts, activated, or not, by the contrapositive operators, what demonstrates that, beyond establishing relations between the terms, in the sense of functioning as cohesive elements, these operators, in the academic abstract genre, are used as argumentative strategy, because they guide the statements to particular conclusions and materialize, in the own statements, many points of view and beliefs that can be contested, or not, by the interlocutor.